Recent progress in visible light-driven halogenation: Chlorination, bromination, and iodination - Nguyen, Anh Thu; Kang, Houng; Luu, Truong Giang; Suh, Sung Eun; Kim, Hee Kwon (Bulletin of the Korean Chemical Society, 2024)
Halogenation is one of the most important transformations in organic synthesis. Halogenated compounds are employed in many reactions to prepare useful molecules. Many methods have been developed to introduce halogens into different compounds. Visible light-mediated reactions are the efficient, low-toxic, and mild-condition methods applied for various organic chemistry transformations. Remarkably, there has been an increasing development in the application of visible light-induced halogenation in recent years. Herein, we present a comprehensive summary of halogenation reactions including chlorination, bromination, and iodination under visible light irradiation since 2020.
Keywords: Bromination; Condition; Halogenated compounds; Iodination; Mediated reactions; Organic synthesis; Photoreactions; Recent progress; Visible light; Visible-light-driven; bromination; chlorination; halogenation; iodination; photoreaction